2023
DOI: 10.1167/iovs.64.12.28
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Upadacitinib on Experimental Autoimmune Uveitis: Insights From Single-Cell Analysis

Zhaohao Huang,
Qi Jiang,
Junjie Chen
et al.

Abstract: Purpose This study aimed to elucidate the impact of upadacitinib, a Janus kinase 1 (JAK1)-specific inhibitor, on experimental autoimmune uveitis (EAU) and explore its underlying mechanisms. Methods We utilized single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) to investigate the JAK/signal transducer and activator of transcription (STAT) pathway in peripheral blood mononuclear cells (PBMCs) of 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In active multiple sclerosis, CXCR4 + leukocytes are trafficked to the brain lesions to cause tissue damage by CXCL12 secreted by endothelial cells [ 75 ]. CXCR4 was also reported to be related to EAU pathogenesis [ 76 ]. The intercellular communication analysis in our study among the retina cells predicted that Cxcl12-Cxcr4 was a significant ligand-receptor pair that was mainly sent by VECs and acted on immune cells, indicating the involvement of CXCR4 in ocular infiltration of immune cells during uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…In active multiple sclerosis, CXCR4 + leukocytes are trafficked to the brain lesions to cause tissue damage by CXCL12 secreted by endothelial cells [ 75 ]. CXCR4 was also reported to be related to EAU pathogenesis [ 76 ]. The intercellular communication analysis in our study among the retina cells predicted that Cxcl12-Cxcr4 was a significant ligand-receptor pair that was mainly sent by VECs and acted on immune cells, indicating the involvement of CXCR4 in ocular infiltration of immune cells during uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Regulation of regulatory T cells: the inhibitory effect of upadacitinib also involves the function of regulatory T cells (Treg). Upadacitinib can increase the number and function of Treg cells, thereby mitigating excessive immune system activation through immune response regulation ( 28 ). Research has indicated that the dynamic evolution of Treg cells, Th17 cells, and other immune cells is closely related to the pathogenesis of gout and the inflammatory response, primarily manifested in T cell-mediated cellular immunity and B cell-mediated humoral immune responses ( 29 ).…”
Section: Discussionmentioning
confidence: 99%